Societal attitudes in ovo gender determination as an alternative to chick culling - Corrinna Reithmayer; Michael Danne; Oliver Mußhoff (Georg-August-Universität Göttingen, Department für Agrarökonomie und Rurale Entwicklung (DARE), 2019)
In ovo gender determination of incubated eggs can be a large-scale substitute to the culling of male chicks in layer hen production. However, the technology raises new ethical concerns which relate to the sensitivity of the embryo, as well as how the screened out eggs will be used afterwards and the accuracy of gender determination. In order to comprehensively investigate consumer attitudes towards this new technology, a questionnaire including a choice experiment was distributed to a representative sample of 482 German consumers between December 2018 and March 2019. The data was analyzed by an explorative factor analysis and a latent class analysis. Results indicate that the sample can be divided into four segments, which differ in preferences for production attributes, attitudes and price sensitivity. Attitudinal differences are found regarding respondents' approval of the technical advances in agricultural production, confidence in legal regulations and the endorsement of enhanced livestock production conditions. Both a meaningful usage of by-products and a high rate of accuracy are crucial factors for the acceptance of in ovo gender determination for the majority of respondents. However, response behavior of one segment, representing 11% of the sample, indicates the disapproval of both chick culling and in ovo screening.
Keywords: 330; chick; choice experiment; culling; gender determination; in ovo; latent class